2005
DOI: 10.1029/2005ja011218
|View full text |Cite
|
Sign up to set email alerts
|

Forecast evaluation of the coronal mass ejection (CME) geoeffectiveness using halo CMEs from 1997 to 2003

Abstract: [1] In this study we have made a forecast evaluation of geoeffective coronal mass ejections (CMEs) by using frontside halo CMEs and the magnetospheric ring current index, Dst. This is the first time, to our knowledge, that an attempt has been made to construct contingency tables depending on the geoeffectiveness criteria as well as to estimate the probability of CME geoeffectiveness depending on CME location and/or speed. For this, we consider 7742 CMEs observed by SOHO/LASCO and select 305 frontside halo CMEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 29 publications
3
44
0
1
Order By: Relevance
“…In previous study, the classification with CME lo- Kernel Parameters : c(C = 2 c ), g(γ = 2 g ) (Kim et al 2005). When comparing these values, we found that the PODn and FAR of the SVM result are slightly lower, but PODy, Bias and CSI are significantly improved.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous study, the classification with CME lo- Kernel Parameters : c(C = 2 c ), g(γ = 2 g ) (Kim et al 2005). When comparing these values, we found that the PODn and FAR of the SVM result are slightly lower, but PODy, Bias and CSI are significantly improved.…”
Section: Resultsmentioning
confidence: 96%
“…Earthward CMEs interact with the Earth's magnetic field and result in geomagnetic storms. There have been many studies on the relationship between CMEs and geomagnetic storms; front-side halo CME (Webb 2002;Gopalswamy et al 2007;Zhang et al 2007), the location of CMEs (Kim et al 2005;Wang et al 2002), the speed of CMEs (Srivastava & Venkatakrishnan 2004), and front-side direction parameter of CMEs (Moon et al 2005;Kim et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Information about CMEs, their velocity and their place of origin on the solar surface enables geomagnetic activity to be forecast 1-3 days in advance (Srivastava 2005;Gleisner and Watermann 2006a, b), the source of the most severe geomagnetic disturbances being CMEs with the highest velocity (Tsurutani 2001;Kim et al 2005). However, the effects in the near-Earth environment critically depend on whether the interplanetary magnetic field in the post-shock solar wind rotates from North to South or vice versa.…”
Section: Predictability Of Space Weathermentioning
confidence: 99%
“…Therefore, new opportunities to improve the scientific knowledge on the triggers of geomagnetic disturbances arise, leading to develop new forecasting tools based on solar observations. These solar-based tools (see e.g., Kim et al 2005;Gleisner & Watermann 2006a, 2006bRobbrecht & Berghmans 2006) are able to forecast in advance -one to three days depending on the solar wind speed -to those prediction schemes based on the knowledge of interplanetary parameters (see e.g., Boberg et al 2000;Gleisner & Lundstedt, 2001a, 2001bLundstedt et al 2002aLundstedt et al , 2002b. For practical applications the first can serve as a preliminary warning, which is then confirmed or cancelled by the latter.…”
Section: Response Of the Terrestrial Environment To Solar Activitymentioning
confidence: 99%